Comprehensive Drug-Class Review Framework for improved evidence-based drug policy and formulary modernization. (3rd December 2020) - Tadrous, Mina; Knowles, Sandra; Ruddock, Brent; Oh, Paul; Mamdani, Muhammad M.; Juurlink, David N.; Gomes, Tara
Abstract: Formularies are used by payers to optimize access and ensure the appropriate use of medications. Lack of follow-up and re-evaluation can lead to outdated formularies that are not reflective of current evidence. Formulary modernization, an approach to re-align formularies with current evidence has proven successful. The Ontario Drug Policy Research Network (ODPRN) launched a framework for conducting comprehensive drug-class reviews. This commentary describes the individual components of this framework and lessons learned through completion of 12 reviews between 2013 and 2016. We present the ODPRN drug-class review of treatments for chronic hepatitis B as a case example to illustrate the components and impact. The incorporation of foundational health technology assessment components such as economic evaluations and knowledge synthesis with contextualizing evidence such as patient and clinician perspectives (through qualitative studies), real-world evidence (through data analytics), and cross-jurisdictional comparisons (through environmental scans and data analytics), successfully developed jurisdictionally specific policy recommendations grounded in up-to-date evidence. The ODPRN framework for conducting comprehensive drug-class reviews is a robust and feasible approach to conduct formulary modernization. This framework allows for actionable and specific policies which are likely to be considered by decision makers. Adoption of similar frameworks in other jurisdictions may improve uptake of evidence-informed policy recommendations.